Dimension synthesis optimization of cat-like robots under multiple constraints - WU Binghui; WEI Zhaoyi; LI Min; CHENG Yintai (Jixie chuandong)
ObjectiveIn order to solve the problem of insufficient parameters optimization with multiple constraints in the current research of cat-like robots, a method of dimension optimization using the grey wolf algorithm was proposed. The sizes of the key components of the cat-like robot were optimized in the method, and higher stability and flexibility of the robot were obtained under the restriction of many constraints.MethodsFirstly, the mechanics of the cat-like robot model was analyzed, and the multi-constraints and objective function were acquired comprehensively. Secondly, the grey wolf algorithm was used to optimize the size of the leg and waist of the robot. Lastly, the simulation analysis of the cat-like robot was carried out in Matlab and Adams software.ResultsThe results show that the stability index is improved by 31.15％, and the flexibility index is improved by 11.28%. It verifies the rationality of the optimization scheme of the robot.